IMPLEMENTASI METODE HALAQAH DALAM MENANAMKAN KARAKTER RABBANI ANAK DI LEMBAGA PENDIDIKAN ISLAM - Makhmudah, Siti (Universitas Islam Malang, 2021)
In the learning there are usually students who are already fluent in reading the Quran, there are students who are very smart or quickin accepting material delivered by the teacher, even memorizing the Knowledge Islamic Education subject matter, and instead there also students who already know the meaning of educational lessons the religion of islam that has been conveyed by the teacher. But the student has not been able to apply it in daily life such as not respecting parents, not respecting the teacher, even not wanting to practice religious teachings islam is like prayer and fasting. In order to instill religious character of children in schools need to be held effective and efficient learning. Role learning methods and deposits are very important because this method is right to develop extra practice of Islamic religious education. This research is aimed to describe how the teacher plants religious characters children at school, in the research method uses qualitative research. The results of this study are: (1) The implementation of memorization and deposit methods by the teacher in instilling religious character in students in the school is the 4545 student memorizing the material and its explanation such as verses of the holy Quran and its translation, students will deposit the memorization results tothe teacher with the target that has been specified in the learning plan. (2) Problems with the implementation of memorization methods and teacher deposits in instilling religious character in students in schools are: students have not been able to read Arabic script, students’ abilities are still lacking, learning media are still minimal. (3) The teacher’s solution in solving the problematic implementation of memorization and deposit methods for inclution of the religious character of student is: students attend extracurricular activies, student are given additional assignments, the teacher makes learning media.